Evaluation of the Wood and Plastic Formworks in Building Construction Industry for Sustainable Development - W. B. Kareem, R. O. Okwori, H. O. Abubakar, A. Nuhu & E. I. Dickson (Covenant Journal of Engineering Technology, 2019)
This research work assessed wood and plastic in building construction. The study was a descriptive survey design and as such made use of questionnaire with 42 items. The Population of the study was 110 respondents which include 40 building professional and 70 non-building professional. The data were analysed using mean and standard deviation. The finding of the study shows that plastic work form can be used for casting slab, concrete wall among others. The finding also revealed some factors that determines the selection of form work such as climatic condition, labour efficiency and that plastic formwork saves cost as a result of long reuse period. It is therefore recommended that; plastic and wooden formwork should be integrated often in the casting of slabs, beam and columns without discrimination, proper adherence to standards and specifications for use of any type of formwork, there should be large scale production of plastic formwork to conserve forest and wood, factors to be considered in the selection of formwork should not be ignored, there should be proper weighing of the advantages and disadvantages of each type of formwork relating to the scale of construction before the choice of any formwork.